Pengaruh Penggunaan Media Webtoon Terhadap Keterampilan Menulis Cerpen Siswa Kelas XI SMA Kristen Abdi Wacana Pontianak - Ester, Tri Windi; Wulan, Adisti Primi; Yuda, Ramadhan Kusuma (Lembaga Intelektual Muda (LIM) Maluku, 2025)
This study aims to determine the effect of webtoon media use on the short story writing skills of 11th grade students at Abdi Wacana Christian High School in Pontianak. The method used is experimental research with a pre-experimental design and a one-group pretest-posttest design. Data collection was carried out using tests and documentation. The research population included all 119 students in the 11th grade at SMA Kristen Abdi Wacana Pontianak, with a sample size of 15 students. Data analysis was performed using a t-test to determine the difference between the pretest and posttest results. The analysis results show that the average pretest score was 41.33, which is considered adequate, while the average posttest score increased to 66.67, which is considered excellent. The t-test results show a calculated t-value of 6.677, which is greater than the table t-value of 2.145 at a significance level of 0.05, indicating a significant difference between before and after the treatment. Thus, it can be concluded that the use of webtoon media has a positive and significant effect on improving the short story writing skills of 11th grade students at Abdi Wacana Christian High School in Pontianak.